2021
DOI: 10.3390/nano11123288
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Calorimetric Analysis of Mixed Micelle Formation from Aqueous Binary Surfactants for Design of Nanoscale Drug Carriers

Abstract: While numerous papers have been published according to the binary surfactant mixtures, only a few articles provide deeper information on the composition dependence of the micellization, and even less work attempts to apply the enhanced feature of the mixed micelles. The most important parameter of the self-assembled surfactants is the critical micelle concentration (cmc), which quantifies the tendency to associate, and provides the Gibbs energy of micellization. Several techniques are known for determining the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The application of micellar systems (monocomponent and multicomponent) in pharmaceutical and food formulations is largely based on the micellar solubilization of poorly soluble (hydrophobic) particles in water. If poorly soluble particles do not have polar groups or have an insufficient number of polar groups, they are incorporated into the hydrophobic core of the micelle (in contrast, if they have sufficient polar groups, they are located near the polar groups of surfactants with which they build hydrogen, dipole–dipole, and ion–dipole interactions, depending on whether the surfactants are ionic or nonionic). …”
Section: Introductionmentioning
confidence: 99%
“…The application of micellar systems (monocomponent and multicomponent) in pharmaceutical and food formulations is largely based on the micellar solubilization of poorly soluble (hydrophobic) particles in water. If poorly soluble particles do not have polar groups or have an insufficient number of polar groups, they are incorporated into the hydrophobic core of the micelle (in contrast, if they have sufficient polar groups, they are located near the polar groups of surfactants with which they build hydrogen, dipole–dipole, and ion–dipole interactions, depending on whether the surfactants are ionic or nonionic). …”
Section: Introductionmentioning
confidence: 99%
“…They have been successfully used to stabilize various nanoscale materials, for example, Se NPs, silica nanospheres, and nanoscale ZnO [ 1 , 2 , 3 , 4 ]. They are one of the most effective stabilizers due to their adsorption ability on the surface of nanoparticles [ 5 , 6 , 7 , 8 ]. Scientists have found that cetyltrimethylammonium bromide (CTAB) can be adsorbed onto silver nanoparticles by strong chemisorption in an aqueous solution, which is accompanied by the stabilization of nanoparticles [ 9 ].…”
Section: Introductionmentioning
confidence: 99%